Attention Deficit Hyperactivity Disorder and Sexual Functioning - is there a connection? - Skwara, Julia; Węgrzyn, Konstancja; Wasilewski, Marcin; Nowicki, Maciej; Laskowski, Gustaw; Góra, Agnieszka; Barański, Dawid; Salińska, Anna; Węgrzyn, Piotr; Dąbrowska, Natalia (Quality in Sport, 2024)
Understanding how ADHD affects sexual functioning is key to providing comprehensive care. This review looks into the current research on sexual health in people with ADHD, focusing on how common sexual dysfunction is, how ADHD symptoms might impact sexual behavior, and what role medications play. By summarizing the existing studies, this review aims to highlight what we don’t know yet and suggest future research to improve treatment and patient outcomes. The review covers literature related to sexual functioning in ADHD, particularly looking at connections to hypersexuality, paraphilias, and various sexual behaviors. A thorough search of electronic databases, including PubMed, PsycINFO, and Google Scholar, was conducted using relevant keywords such as 'ADHD,' 'hypersexuality,' 'paraphilias,' 'sexuality,' 'sexual behavior,' and 'sexual violence.' The study duration was 6 months. Common features of ADHD, such as impulsivity, poor impulse control, and difficulties with self-regulation, may contribute to risky sexual behaviors, compulsive sexual behavior, or the development of paraphilic interests. It's important for doctors dealing with ADHD in children to discuss sexual health as the patient nears adolescence and offer guidance on safe sex. Treatment should combine medication with therapy. Since impulsivity seems to play a big role in risky sexual behavior, making contraceptives readily available could be important for sexual health. Longitudinal studies are necessary to better understand the temporal relationships and progression of sexual behaviors and ADHD symptoms over time. Given the potential impact of ADHD on sexual behavior and functioning, healthcare providers should consider screening for ADHD in patients presenting with issues related to hypersexuality, paraphilias, or other sexual concerns.